Letter to Thomas Lynch from Jane Tolmach - Jane Tolmach:::::: (1967)
A letter in which Jane Tolmach congratulates Thomas C. Lynch on organizing a California Democratic delegation to the National Convention in support of President Johnson and expresses her strong endorsement of the effort. She outlines her role as Women's Chairman-South, describing the active Women's Division organization she has built across eight Southern California counties and her connection with approximately 10,000 Democratic women. Tolmach offers her assistance, including serving on the delegation's steering committee, emphasizing her organizational experience and working relationships throughout Southern California.